Determinants, Reliability and usefulness of a bench press repeated power ability test in young basketball players - Gonzalo-Skok, O.; Tous-Fajardo, J.; Arjol-Serrano, J. L.; Mendez-Villanueva, A. (The Journal of Strength and Conditioning Research, 2014)
The aim of the present study was to analyze the main determinants of an upper-body repeated power ability (RPA) test and to examine its reliability and usefulness. Forty-five highly trained, male, young basketball players performed the RPA test (5 sets of 5 repetitions with 30 seconds of passive recovery within sets) on 2 sessions separated by 5-7 days. Power output was registered using a linear encoder attached to the barbell. Results showed no significant differences (p > 0.05) between each set in both sessions and trivial (<0.2) effect sizes in all the analyzed variables. For every set, intraclass correlation coefficient was very high (0.96-0.98) and coefficient of variation was low (3.3%-4.3%). Because the typical error of measurement values were lower or similar than the smallest worthwhile change (SWC0.2 = 0.2 × between-subject SD), the usefulness of most variables was rated as "good" or "OK" considering that small changes would be detected by this test. The percentage of power decrement could only be used to detect large effects (>1.2 × between-subject SD). An almost perfect correlation (r = 0.99; 90% confidence interval, 0.98-0.99) was found between the average power in set 1 (APbest) and the average power over 5 sets (APmean). In conclusion, the main determinant of RPA test is APbest, and because of the high reliability scores obtained, this protocol may be used to assess upper-body RPA in relatively experienced young athletes.